Incidentally Detected Oropharyngeal Squamous Cell Carcinoma on 18F-Fluciclovine PET/CT. (May 2019) - Raghavan, Kesav; Wen, Kwun Wah; Small, Eric J.; Ha, Patrick; Flavell, Robert R.
Abstract : Abstract: We present a case of oropharyngeal squamous cell carcinoma (SCC) of the tongue base incidentally detected on 18 F-fluciclovine PET/CT. A 79-year-old man with history of locally advanced prostate cancer (Gleason score 4 + 5 = 9; cT2cN1M0) previously treated with androgen deprivation therapy (luprolide + bicalutamide) presented with a slowly rising serum prostate-specific antigen over 3 years, concerning for recurrent disease. 18 F-fluciclovine PET/CT, obtained to identify potential sites of recurrence, demonstrated prostate bed uptake with possible left seminal vesicle involvement. Additionally, an exophytic, tracer-avid right tongue base mass was incidentally noted and later confirmed to be p16+ SCC on biopsy.